Comparative thermal study of heavy crude oils by DSC. (16th February 2016) - Mothé, Michelle Gonçalves; Perin, Mauricio; Mothé, Cheila Gonçalves
ABSTRACT: Crude oil represented 50% of primary energy consumption in the world at the beginning of this decade. For each reservoir existent of conventional petroleum or gas there is three times the amount of heavy crude oil in the planet. The present work investigates the thermal behavior of three heavy crude oils from Brazilian basins. It was possible to make an interesting comparison for the same petroleum due to the use of different DSC equipment, especially for the extra heavy crude oils. The petroleum sample with the lowest °API exhibited the highest value for specific heat capacity between all studied samples.